Increased Student Participation in Online Lectures (International Journal of Education and Literature, 2023)
Online lectures have become the wrong option in our digital age. Therefore, in this online lecture procedure, the lecturer was required to be able to produce media and lecture approaches. A favorable learning environment, student participation, lecturer performance during instruction, lecture media, and method are a few of the variables that affect the attainment of lecture skills. This study aims to investigate and characterize the efforts made by lecturers to increase student engagement in online courses. This study used a case study approach to qualitative research as its methodology. The study's findings indicate that there are numerous challenges facing online lectures in the current digital era, including a dearth of engaged students, a lack of infrastructure and resources for lecturers and students, as well as network and Internet issues and data availability quotas. All of the lectures given in online classrooms by professors have an impact. The study's findings suggest that lecturers should try to be innovative and creative during the stages of preparing, implementing, and evaluating lectures online.